Natural Born Copycat Killers and the Law of Shock Torts - John Charles Kunich (Washington University Law Quarterly, 2000)
This Article explores the legal ramifications inherent in the putative links between violent deaths—both homicides and suicides—and various entertainment industry products, including motion pictures, television programs, video games, and musical recordings. We briefly review some examples in which popular entertainment-media allegedly played a significant role in spurring individuals to commit acts of violence against themselves or others. While some of these violent events have been widely reported, others are less well known. In any event, we provide some factual predicate in order to establish the context for one of the most controversial legal issues of modern times. Then we examine the possibility of redress for the survivors of such tragedies through the legal system. Plaintiffs in these cases be the persons or their survivors (e.g., their parents) who absorb these shockingly violent entertainment-media messages and act them out by injuring or killing themselves. Plaintiffs can also be victims (or their survivors) injured or killed by violence acted out by others who have been exposed to shockingly violent forms of entertainment-media. We propose survivors of media-related tragedies seek redress with a new cause of action we have termed “shock torts.” We will discuss in detail multiple legal theories that potentially offer redress for harms caused by shock torts. We also analyze the primary obstacles to successful shock tort litigation, with emphasis on First Amendment concerns that stand as the main barrier to recovery. In the course of parsing the traditional modes of analysis, we propose a new test for evaluating the extent of First Amendment protection appropriate for defendants in these complex and difficult cases.
Keywords: Freedom of speech; Violence; Motion pictures; Video games; Music; Tort theory; Inchoate offenses; Movie violence; Wrongful death